2022
DOI: 10.3389/fpls.2022.837994
|View full text |Cite
|
Sign up to set email alerts
|

An Easy and Rapid Transformation Protocol for Transient Expression in Cotton Fiber

Abstract: Cotton fiber is the most important natural textile material in the world. Identification and functional characterization of genes regulating fiber development are fundamental for improving fiber quality and yield. However, stable cotton transformation is time-consuming, low in efficiency, and technically complex. Moreover, heterologous systems, such as Arabidopsis and tobacco, did not always work to elucidate the function of cotton fiber specifically expressed genes or their promoters. For these reasons, const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The efficiency of Agrobacterium -mediated transient expression is affected by concentration, infiltration time, and acetosyringone (AS) concentration, whereas the efficiency of biolistic-mediated transient expression is affected by gold particle concentration, bombardment distance, and helium pressure [ 6 ]. In recent years, transient expression systems have ceased to be exclusive to model plants, such as Arabidopsis [ 8 ] and Nicotiana benthamiana [ 9 ], and individual transient expression systems for many economically important plants, such as cotton [ 10 ], Ricinus [ 11 ], citrus [ 12 ], Chenopodium quinoa [ 13 ], and Vigna unguiculata [ 14 ], have been established. However, compared to these economic crops, the establishment of transient expression systems in medicinal plants are very much behind, which may leave the functions of genes incomplete and hinders the development and utilization of these natural medicinal values by humans.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of Agrobacterium -mediated transient expression is affected by concentration, infiltration time, and acetosyringone (AS) concentration, whereas the efficiency of biolistic-mediated transient expression is affected by gold particle concentration, bombardment distance, and helium pressure [ 6 ]. In recent years, transient expression systems have ceased to be exclusive to model plants, such as Arabidopsis [ 8 ] and Nicotiana benthamiana [ 9 ], and individual transient expression systems for many economically important plants, such as cotton [ 10 ], Ricinus [ 11 ], citrus [ 12 ], Chenopodium quinoa [ 13 ], and Vigna unguiculata [ 14 ], have been established. However, compared to these economic crops, the establishment of transient expression systems in medicinal plants are very much behind, which may leave the functions of genes incomplete and hinders the development and utilization of these natural medicinal values by humans.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton fiber quality is an important agronomic trait; therefore, significant efforts have been made to study its biological mechanisms [ 31 , 32 , 33 , 34 , 35 ]. In recent years, several key genes involved in fiber development have been reported [ 36 , 37 , 38 , 39 , 40 ], which have greatly contributed to the study of fiber development mechanisms, and studies have shown that hormones, functional genes, and transcription factors form a complex regulatory network that coordinates the dynamic fiber development process [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6]. In recent years, the transient expression system is no longer exclusive to model plants such as Arabidopsis [8] and Nicotiana benthamiana [9], many economic plants such as cotton [10], ricinus [11], citrus [12], Chenopodium quinoa [13], and Vigna unguiculata L. [14] have also established their own transient expression systems. However, there are still few medicinal plants possessing their own transient expression system.…”
Section: Introductionmentioning
confidence: 99%